Investigating the morphological form مَفْعَل -An editing study- - Yhia Mohemeed , Ma’an; Adeeb Ramdaan, Shaiban (Journal of College of Education, 2020)
The current study invesitigates the words in the morphological form of مفعل in a book written by Mohmeed bin Ali Al-Sbaan (d. 1206 A.H) . We have strived that our work will be continuous in editing manuscripts heritage of our rich language, especially those manuscripts dealing with the Arabic morphology; The manuscript deals with the study of the derivation and the morphological explanation of the methods of the 13th century AH scholars. The sources that the author benefited from in his book were rich and highly valued, which brought together the writings and doctrines of the applicants and their doctrines, and those of the later and their interventions, and the change in opinions, responses, differences, and terminology, and the message was truly a painting that included many scientific arts. And color it in the language of the dictionary, and decorate it with explanation, and explain it with an interpretation of many of its difficult words . When the investigation was an art of beauty, and a form of taste and expression, the message presented us with a form and an output of a number of benefits that represented the era of his authorship, and embodied the nature of the prevailing arts of his era, starting with the type of pen used in writing through the supply and its types, and not the last with the decoration accompanying the explanation, as well as Mold type Used, and the added amendments and comments that accompany the explanation lead to it, despite the fact that the unique version that we adopted in the investigation followed the era of the author by a century, i.e.: in the twelfth century, but its copying from the scientific environment itself; so the eleventh era was measured by the twelfth, and it is without Doubt one of the underpinnings of investigation related to this art.